2016
DOI: 10.4137/nmi.s32909
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Properties of Red Wine Compounds and Cardiometabolic Benefits

Abstract: Wine has been used since the dawn of human civilization. Despite many health benefits, there is still a lot of discussion about the real properties of its components and its actions on cells and molecular interactions. A large part of these issues permeate the fine line between the amount of alcohol that causes problems to organic systems and the amount that could be beneficial for the health. However, even after the process of fermentation, wine conserves different organic compounds from grapes, such as polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 77 publications
1
94
0
2
Order By: Relevance
“…These differences could be related to the modulatory effect of the non-alcoholic fraction of red wine (i.e., polyphenols, glycerol, and polysaccharides). [34] Cotinine, caffeine, inositol, and piperine were found to be positively associated with RWC. Cotinine is an alkaloid found in tobacco and is also the predominant metabolite of nicotine.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These differences could be related to the modulatory effect of the non-alcoholic fraction of red wine (i.e., polyphenols, glycerol, and polysaccharides). [34] Cotinine, caffeine, inositol, and piperine were found to be positively associated with RWC. Cotinine is an alkaloid found in tobacco and is also the predominant metabolite of nicotine.…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to their results, we found no associations with LPCs, whereas we reported different positive/negative associations with some species of TAGs. These differences could be related to the modulatory effect of the non‐alcoholic fraction of red wine (i.e., polyphenols, glycerol, and polysaccharides) …”
Section: Discussionmentioning
confidence: 99%
“…However, resveratrol by enzymatic hydrolysis of its glycosides can lead to free trans-and cis-resveratrol structures, whose concentration depends on grape variety, possible fungal contamination and climatic conditions, which conditions its variation [19]. On the other hand, studies have demonstrated that the vinification process is the factor responsible for the high levels of resveratrol in red wines, when compared to white wines [48].…”
Section: Phenolic Composition Of the Wines And Its Antioxidant Activimentioning
confidence: 99%
“…The choice of samples was due to the fact that Syrah and Cabernet Sauvignon grapes are among the main varieties used in the elaboration of red wines in the São Francisco Valley and are pointed as important for winemaking in Brazil [16]. In addition, the demand and appreciation of the Syrah and Cabernet Sauvignon wines have been verified in the national and international markets [17,18,19,20].…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation